Parkinson's disease fluid biomarkers for differential diagnosis of atypical parkinsonian syndromes - Jun Yang; Ayotimofe Idowu; Liana Rosenthal; Xiaobo Mao (Wiley, 2023)
Abstract The scope of the present review is to synthesize existing literature data on fluid biomarkers for Parkinson's disease (PD) and atypical parkinsonian syndromes (APS). Parkinsonian syndromes encompass a body of heterogeneous neurodegenerative diseases marked by characteristic movement dysfunction, among which PD is the most prevalent form. In addition to the stereotypical presentation of PD, patients may also manifest atypical symptoms that raise the suspicion of APS, such as PD with dementia, progressive supranuclear palsy, multiple system atrophy, dementia with Lewy body, and corticobasal degeneration. Clinical diagnosis of PD and APS depends heavily on patients' presenting symptoms without reliable objective tests or imaging studies. Fluid biomarkers are powerful tools that facilitate diagnosing and monitoring various parkinsonian syndromes. Therefore, establishing parkinsonian biomarkers is a necessary step in the scope of basic science research and clinical practice. This review will discuss some of the past decade's most promising cerebrospinal fluid and other fluid biomarkers. We highlighted the shortcomings of alpha‐synuclein (α‐syn), Aβ42, and tau as differences in the expression of these proteins are moderate at best. Protein misfolding cyclic amplification and real‐time quaking‐induced conversion are novel techniques with remarkable discriminatory capacity for PD and APS. Autoantibodies have also introduced a marker for possible early diagnosis and staging for PD. Neurofilament light chain and microRNAs are promising fluid biomarkers that may be more suitable as biomarkers compared to α‐syn, Aβ42, and tau. At its current stage, fluid‐based biomarkers have improved significantly in diagnosing PD from healthy controls and differentiating between PD and APS, but insufficient for clinical usage due to a lack of validation and limitation in discriminatory power.